Critical thinking a concise guide - Bowell, Tracy 1965-; Kemp, Gary 1960- (Routledge, 2010)
Critical thinking: a concise guide is a much-needed guide to argument analysis and a clear introduction to thinking clearly and rationally for oneself. Through precise and accessible discussion this book equips students with the essential skills required to tell a good argument from a bad one. This third edition has been revised and updated throughout, with new exercises, and up-to-date topical examples, including: "real-world" arguments; practical reasoning; understanding quantitative data, statistics, and the rhetoric used about them; scientific reasoning; and expanded discussion of conditionals, ambiguity, vagueness, slippery slope arguments, and arguments by analogy.
Includes bibliographical references and index
Keywords: Argumentatie; Cognitieve vaardigheden; Kritisch denken; Redeneren; Theorie en praktijk; Critical thinking; Kritisches Denken; Argumentation; Lehrbuch